Understanding of Menstruation on Anxiety in Facing Menarche Among 4th–6th Grade Students at SDN Tebon, Barat District, Magetan Regency - Mertisa Dwi Klevina; Irmawati Mathar (Journal of Asian-african Focus in Health, 2026)
Menarche is a major developmental event for girls because it marks the beginning of reproductive maturity and requires both physical and psychological adjustment. Limited knowledge about menstruation may cause fear, confusion, and anxiety, especially among elementary school students who have not yet experienced their first menstruation. This study aimed to determine the relationship between knowledge about menstruation and anxiety in facing menarche among female students in grades 4 to 6 at SDN Tebon, Barat District, Magetan Regency. This study used a quantitative correlational design with an analytical survey and a cross-sectional approach. The sample consisted of 32 female students who had not experienced menarche and met the study criteria. Data were collected using a menstruation knowledge questionnaire and the Zung Self-Rating Anxiety Scale. Data were analyzed using descriptive statistics and the Spearman Rank correlation test with a significance level of 0.05. The results showed that most respondents had moderate knowledge about menstruation, accounting for 14 students or 43.8%. Anxiety in facing menarche was mostly in the moderate category, with 12 students or 37.5%. The Spearman Rank test showed a significant relationship between knowledge about menstruation and anxiety in facing menarche, with a p-value of <0.001 and a correlation coefficient of 0.873. These findings indicate a very strong relationship, where better menstrual knowledge is associated with lower anxiety. The study concludes that early menstrual education is needed at the elementary school level to improve readiness, reduce fear, and support girls in facing menarche more confidently.